A primer on contrast agents for magnetic resonance imaging of post‐procedural and follow‐up imaging of islet cell transplant - Anessa Puskar; Bara Saadah; Asad Rauf; Szymon R. Kasperek; Muhammad Umair (Nano Select, 2023)
Abstract β‐islet cell transplantation is a promising proposed treatment for type 1 diabetes mellitus (T1DM) which can provide more physiological glucose control when compared to exogenous insulin therapy and reverse secondary consequences of diabetes. Unfortunately, β‐islet cell transplantation is not a permanent solution for patients with T1DM as 85–90% of β‐islet recipients return to exogenous insulin treatment within 5 years of the transplant. Despite its lack of success, β‐islet cell transplantation still has potential for the treatment of T1DM and significant work has been done to non‐invasively quantify β‐islet cell concentrations in transplantation to better understand the mechanism of β‐islet cell rejection. While several imaging modalities have been utilized, magnetic resonance imaging (MRI) remains at the forefront of β‐islet cell imaging due to its high resolution and lack of radiation exposure to patients. Several MRI contrast agents have been explored for the imaging of β‐islet cells including superparamagnetic iron oxide nanoparticles (SPIONs), gadolinium‐based contrast agents (GBCA), manganese (II), fluorine‐19, and theranostic agents, with SPIONs being the most extensively studied. In this review, we provide an overview of the history, recent progress, and challenges of MRI in islet transplantation with a focus on the molecular imaging agents used.